The effect of Zingiber cassumunar Roxb rhizome extract on in vitro phagocytic activity and lymphocyte proliferation - Nurkhasanah Mahfudh; Nanik Sulistyani; Dinda Anindya Sabillah (Pharmaciana, 2020)
Zingiber cassumunar Roxb (bengle) is one of the plants with the potential as an immunomodulator. It contain curcumin and some volatile compounds which previously reported to be potential as immunomodulator. This study aims to examine and determine the effect of ethyl acetate fraction of bengle extract on phagocytic activity of macrophages and lymphocyte proliferation in vitro. The bengle rhizome is macerated with 96% etanol solvent and then followed by ethyl acetate fractionation. The macrophage and lymphocyte were used in this study was isolated from male Balb/C strain mice. The macrophage phagocytosis activity was carried out using latex bead assay, and lymphocyte proliferation assay was carried out using MTT assay method. The concentration of extract was used in this study were 25, 50 and 100 Î¼g/mL. The effect of treatment was compared to negative control group. Â The results showed that ethyl acetate fraction of bengle extract can increase the phagocytic activity of macrophages was shown by increasing of active phagocytes cells (SFA) and phagocytosis index. The highest percentage of SFA and phagocytic index results were shown at a concentration of 100 Î¼g/mL. The results showed that ethyl acetate fraction of bengle extract could increase lymphocyte proliferation significantly compare to the negative control (p<0.05). This study showed the potential of bengle as immunomodulatory agent.